Strengthening Character Education Through E-Book During the COVID-19 Pandemic - Sitti Rahmawati; Hamsar Hasfat (Fakultas Sastra - Universitas Muslim Indonesia, 2021)
The purpose of this study was to explore on strengthening character education through e-books for online or distance learning in the times of COVID-19. The present study employs a descriptive qualitative with the aim of being able to provide clear, objective, systematic, analytical descriptions and information, and critical aspect of Character Education-Based E-book for learning during the Covid 19 era in higher education. There were several steps such as collecting the required data, then classification and description were carried out. The sources of data in this study were government policies, books and articles concerning the implementation of distance learning during the covid 19 period and character education. The method used to collect research data is in the form of literary data that has been selected, searched, presented and analyzed. The application of Indonesian e-books based on character education is a solution that can be done to overcome the problems of character education during the COVID-19 era, especially regarding the use of diction and literature. In this e-book character values ​​can be inserted in the introduction, materials, and assignments to provide character education to students. Hence, the e-book was developed based on the curriculum and the values ​​of character education. E-books are provided in online learning and can be studied by students from their homes both online and offline. In order to draw students’ attention, the e-book must be designed to be visually attractive so that the material in it can be learned and easily understood by students.